유럽연합 경쟁법 집행과정에서의 글로벌 기업들의 대응수단으로서의 자료접근권 - 이호선(Lee, Ho-Sun) (Tonga pŏphak, 2013)
글로벌 기업들의 입장에서 해외의 경쟁법규범은 국내법 이상으로 현실적인 구속력을 가진다. 이들이 담합 혐의 등으로 해외 경쟁당국에 의하여 조사, 처벌의 대상이 되는 것은 이제 흔한 일이 되어가고 있고, 이들의 기업결합 행위 등은 국내에서 뿐만아니라 해외 경쟁당국의 승인 대상이 되고 있다. 이에 본 글에서 저자는 유럽연합의 경쟁법 집행절차에서 이러한 글로벌 기업들이 자신을 방어하기 위해 취할 수 있는 절차적 권리를 특히 자료접근권의 관점에서 분석함으로써 우리 기업들의 가능한 대응전략이 무엇인지 고찰하고자 하였다. 유럽연합의 경쟁법 집행 과정에서 피심인 사업자들은 경쟁법령에 특유한 자료접근권을 행사할 수 있는 바, 원칙적으로 방어권 행사를 위해 모든 자료에 대한 접근 허용이 가능하되, 다만 영업기밀 등 예외적인 경우에는 불허되고 있다. 자료접근의 허부를 둘러싼 분쟁은 청문관을 통해 일차적으로 해결을 모색할 수 있고, 그와 별개로 옴부즈만에 대한 진정을 통해 자료접근을 꾀할 수도 있다. 비록 옴부즈만이 경쟁법 관련 사안에 개입하는 명문의 근거는 없지만 실제로 옴부즈만은 절차적 권리와 관련하여 적극적인 역할을 해 오고 있다. 따라서 글로벌 기업들은 유럽연합 경쟁법 절차들 외에 옴부즈만에 대한 진정절차를 활용할 수 있다는 점을 염두에 두는 것이 좋다. 마지막으로 피심 사업자들의 입장에서는 경쟁법 위반으로 처벌 받고 난 뒤 소비자나 경쟁사업자들과 같은 제3자들로부터의 손해배상청구 소송을 염두에 두어야 한다는 점을 지적해두고자 한다. 이런 소송에 대비하기 위하여 EU 경쟁당국에 제출하는 문서에 기밀을 특정하는 등 조치를 취함으로써 영업이익이 노출되거나, 제출된 자료들이 원고에 의해 손해배상책임의 입증자료로 활용되지 않도록 해야 할 것이다. From the perspectives of global undertakings, the international competition norms have real and legal binding effect on their business than any other domestic laws. It is not surprising and frequently occurred that they have been investigated and punished by the competent competition authorities abroad due to violating anti-trust law. Moreover, the mergers tried by those companies are subject to the approval of the abroad authorities as well as domestic one. Thus, in this article, the author tries to review the strategy of our global corporates for defending themselves in EU competition law enforcement procedures, in particular, focusing on the right to information. Under the EU competition law, the undertakings alleged to violate the competition law are allowed to access all the documents concerned to defend themselves. However, there are some exceptions; for example, the documents contain the trade secrets of other companies. If the disputes over whether or not to allow the right of file access occur, firstly, this matter may be referred to the Hearing Officer, and apart from this, the undertakings may complain to the Ombudsman. Although there are no explicit ground for Ombudsman’s intervening on competition matters, in practice, it has played active role in defending the procedural rights of the alleged firms. Therefore, it is recommendable that the global firms should take in mind to use Ombudsman complaining procedures as well as the EU competition ones. Finally, it should be noted that the alleged undertakings have to prepare responding to damages litigation from the third parties, e.g. consumers or their rivals, after punished for violation on EU competition law. To defend this litigation, by specifying confidential part on the documents required by the EU competition authorities, they must be careful not to disclose their trade secrets, or those documents not to be used as evidences for their civil responsibilities to plaintiffs. KCI Citation Count: 1